ASSESSING THE STUDENTS’ READING COMPREHENSION USING CONFERENCE TECHNIQUE - Firmansyah , Muhammad Eka; Wiyaka; Prastikawati, Entika Fani (FKIP Unismuh Makassar, 2024)
Reading comprehension involves the interaction of the reader, text, and context. Reading comprehension is important because enhances understanding of text and know the detail of the text. This research aimed to improve the student’s comprehension in reading the text and as a medium for assessing English students' reading. The research was undertaken in Junior High School (SMP) N 6 Semarang. The research chose one class and the sample consisted of 34 students in 8C. The researchers used ex-post facto and this research used a quantitative method to measure how well they comprehend the text and assessed two tests to students. The first test was assessed multiple choice test and the second test was assessed conference technique. The data was collected by providing 25 questions using multiple choice test and giving a descriptive text using conference technique. The data analysis technique used ordinary scoring for multiple choice test and a rubric for conference technique. The researchers analyzed the collected data by using paired sample t-test. The result of two tests analysis showed that the value of Sig. (2-tailed) is 0.000 < 0.005, so it means that there is a significant difference reading comprehension when students assessed with different instruments, which is multiple choice test and conference technique and mean of multiple-choice test is 79.05 and mean of conference technique is 86.85, it can be concluded that mean of conference technique is higher than multiple choice, so there is difference between two tests. The last, the result of multiple-choice test and conference technique proved that these two tests have an improvement or significance in students’ reading comprehension.